2008
DOI: 10.1021/jp800753n
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Reaction between Pressure-Frozen Acetonitrile Phases α and β

Abstract: The balance of weak CH...N bonds involving the H 3C- and -CN groups has been related to the structural rearrangement between centrosymmetric and polar acetonitrile structures. The linear highly polar molecules arrange antiparallel in phase alpha below a freezing temperature of 225 K/0.1 MPa and above a freezing pressure of 0.38(5) GPa/296 K and in a polar mode in phase beta below 206 K/0.1 MPa and at pressures higher than 0.63(5) GPa/296 K. The alpha <--> beta phase transition has been considered as a supramol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 43 publications
7
43
0
Order By: Relevance
“…In agreement with the previous work, [11,[13][14][15] the in situ Raman spectra indicate that acetoni- In agreement with the previous work, [11,[13][14][15] the in situ Raman spectra indicate that acetoni-…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with the previous work, [11,[13][14][15] the in situ Raman spectra indicate that acetoni- In agreement with the previous work, [11,[13][14][15] the in situ Raman spectra indicate that acetoni-…”
supporting
confidence: 91%
“…Finally, it transforms into a graphitic polymer by eliminating ammonia. In agreement with the previous work, [11,[13][14][15] the in situ Raman spectra indicate that acetoni- It highlights the fact that very inert CÀH can be activated by high pressure, even at room temperature and without a catalyst.…”
supporting
confidence: 91%
“…Nevertheless, there have been limited reports on structural changes of hydrogen-bonded supramolecular materials under high pressure. 18,19 Recently, we have carried out high-pressure studies on melamine-boric acid adduct (M · 2B) and have shown that M · 2B undergoes a reversible pressure-induced amorphization. 20 Morrison studied temperatureand pressure-induced proton transfers in the hydrogen-bonded adduct formed between squaric acid and bipridine.…”
Section: Introductionmentioning
confidence: 99%
“…After the purification and identification of the product by IR, 1 H‐NMR, 13 C‐NMR, and X‐ray, 2,6‐dimethylpyrimidin‐4‐amine ( 3 ) was obtained as the main product. Under these conditions, in addition to the reaction of imidoyl chlorides 1a with l ‐proline, in the presence of NaH, three molecules of acetonitrile were condensed to produce compound 3 (Scheme ) . The single‐crystal X‐ray analyses confirm the structure of the 2,6‐dimethylpyrimidin‐4‐amine ( 3 ).…”
Section: Resultsmentioning
confidence: 93%